Analysis of the characteristics of optical coherence tomography angiography for retinal cavernous hemangioma: A case report. Issue 7 (February 2018) - Lyu, Shuyuan; Zhang, Ming; Wang, Ruikang K; Gao, Yunxia; Zhang, Qinqin; Min, Xiaoxue
Abstract: Rationale: Retinal cavernous hemangioma is a rare congenital vascular malformation with typical fundus changes. Optical coherence tomography angiography (OCTA), which is in rise in the recent years, is a rapid and noninvasive technology to assist in obtaining information regarding the blood flow changes in the fundus lesions from different layers without injecting a contrast agent. Patient concerns: A 40-year-old male patient with visual occlusion in the right eye for >1 month was reported. Diagnoses: Retinal cavernous hemangioma was diagnosed by fundus examination, fluorescein angiography (FA) and OCTA, and the characteristics of OCTA images were analyzed. Interventions: The lesion occurred outside the macula, the central vision remained basically normal, and no significant complications were noted in this patient. Therefore, we preferred to regularly follow-up without therapeutic intervention. Conclusions: OCTA can display fundus blood flow and vascular lesions noninvasively and rapidly. On OCTA, retinal cavernous hemangiomas showed characteristic changes and have good correspondence with fundus imaging and FA examinations. Moreover, OCTA remains more sensitive to vascular abnormalities, and imaging remains clearer, providing new diagnosis and follow-up route for this disease.